Linguistic Distance, Networks and Migrants' Regional Location Choice - Julia Bredtmann; Klaus Nowotny; Sebastian Otten (Institute of Labor Economics (IZA), 2017)
This paper analyzes the interaction between migrant networks and linguistic distance in the location choice of migrants to the EU at the regional level. We test the hypothesis that networks and the ability to communicate in the host country language, proxied by linguistic distance, are substitutes in the location decision. Based on individual level data from a special evaluation of the European Labour Force Survey (EU-LFS) and a random utility maximization framework, we find that networks have a positive effect on the location decisions while the effect of linguistic distance is negative. We also find a strong positive interaction effect between the two factors: networks are more important the larger the linguistic distance between the home country and the host region, and the negative effect of linguistic distance is smaller the larger the network size. In several extensions and robustness checks, we show that this substitutable relationship is extremely robust.
Keywords: F22; J61; R23; 330; location choice; ethnic networks; linguistic distance; EU migration; multilateral resistance